(untitled) (Revista de Estudos da Linguagem, 2002)
This paper investigates the morphology of truncation andreduplication processes in Brazilian Portuguese (BP). Truncation(also known as abbreviation) is the word formation process inwhich a word is shortened without loss any meaning. I argue thatthe BP’s truncated forms tend to be disyllabic and the secondarystress rhythm also plays a role in the process. The reduplicationinvolves copy of a piece or a complete word, promoting a newlexical item. There are several kinds of reduplication (cf. COUTO,1999), for the moment I will focus only on the total reduplicationverbi-verbi. I will show that both processes are regular andpredictable. Similarly, I will show the tendency of this wordformation to have an open final syllable and binary feet, offeringargument to the Emergence of the Unmarked Theory.